Robust practices for managing maritime supply chain risks: A survey of Nigeria’s seaports - John Nsikan; Rawlings Micheal; Ogbari Mercy; Ariyo Adebukola; Ine Briggs; Daniel Inegbedion (Asian Journal of Shipping and Logistics, 2023)
Managing risks is crucial for efficient and resilient maritime supply chain. For Nigeria’s seaports, the sources of supply chain risks and the best practices for managing them is yet to be sufficiently understood. This paper leveraged the experiences of 67 seaport operators, cargo owners, and shipping professionals in Nigeria to delineate the robust practices in managing supply chain risks. Data collection was via the structured questionnaire and analysed descriptively. Results identified nine main sources of seaport supply chain risks with congestion within port terminals ranked the highest. In addition, six practices were considered as robust for managing seaport supply chain risks: Developing risk feedback mechanism; frequent risk assessment; risk mitigation documentation; keeping records of disruption incidents; regular cargo status update; and better stakeholder relationship management. We recommend that increased level of investment in port digital technologies and regular capacity building in supply chain risk management could be provide the relevant intervention for resilient seaport operations in Nigeria.